Listen to patient’s complaints more than ECHO - Kim, Ho Jin; Kim, Joon Bum (Journal of Thoracic Disease, 2016)
The increasing amount of electronically stored clinical data in modern health care system has heralded an era of big medical data (1). Consequently, utilizing these big data has become a major interest in performing clinical research. Big data-driven clinical research is increasingly important and it is expected to be a viable alternative for prospective randomized controlled trial (RCT) in the future (2,3). Some researchers have argued that the conclusions from the analysis of big data may be more clinically relevant than those from RCT in a real world setting because strict experimental requirements for interventional protocols and subject selections in RCT are hardly reproducible during routine clinical practice (2).